No stone unturned : a history of farming, landscape and environment in the Scottish Highlands and Islands - Dodgshon, R. A. (Robert A.) (Edinburgh : Edinburgh University Press, 2015)
A one-stop text for the long-term history of the Highland countryside, one nuanced in ways that address topical themes like landscape and environmental change. Starting with prehistory, the book examines the way in which the farming community was organised: its institutional basis, its strategies of resource use and how these impacted on landscape, and the way in which it interacted with the challenges of its environment. It carries these themes forward through the medieval and early modern periods, rounding off the discussion with a substantive review of the gradual spread of commercial sheep farming and the emergence of the crofting townships over the eighteenth and nineteenth centuries. Throughout, it draws out what changed and what was carried forward from each period so that we have a better understanding of the region's dynamic history, as opposed to the ahistorical views that inevitably flow from a stress on cultural inertia. Key Features:. Synthesises a great deal of work on the Highland farming community during the medieval and early modern periods in terms of its institutional organisation, resource exploitation, landscape impacts and interactions with environment so as to produce an overall review from prehistory down to 1914. Introduces new ideas and arguments that have not been treated or previewed in other published work. Provides the most substantive review of the continuity/discontinuity debate in the Highland landscape currently available.
Writing the history of Highland farming, landscape and environment -- The prehistoric footprint -- Prehistory into history -- The late medieval and early modern landscape : stasis or change? -- On the eve of the change : a look through the surveyor's eye -- The Highland Toun through time : an interpretation -- Landscapes of change, 1750-c.1815 : the broadening estate -- Landscapes of sheep, deer and crofts : change after c.1815 -- The years of change : an overview.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Agriculture -- Scotland -- Highlands -- History; Traditional farming -- Scotland -- Highlands -- History; Islands -- Scotland -- History; Highlands (Scotland) -- Historical geography; Agriculture -- Écosse -- Highlands -- Histoire; Agriculture traditionnelle -- Écosse -- Highlands -- Histoire; Îles -- Écosse -- Histoire; Highlands (Écosse) -- Géographie historique; TECHNOLOGY & ENGINEERING -- Agriculture -- Agronomy -- Crop Science; TECHNOLOGY & ENGINEERING -- Agriculture -- Agronomy -- General; HISTORY -- General; Agriculture; Historical geography; Islands; Traditional farming; Scotland; Scotland -- Highlands; History